Maryam's story: An ethnographic memoir. Issue 1 (April 2020) - Lindisfarne-Tapper, Nancy; Tapper, Richard
Abstract : In the early 1970s we made more than 100 hours of tape recordings, as part of our ethnographic fieldwork among the Piruzai, Pashtun farmers and semi-nomadic pastoralists in northern Afghanistan. These village voices create a remarkable community self-portrait of a social world now lost and irretrievable. Maryam's story is the perfect exemplar of an unconventional form of auto-ethnography. Maryam was married some thirty years before, as part of a series of marriage exchanges intended to settle a feud between the two main Piruzai families. Her husband, Tuman, became village headman, a Haji, and in 1971 our host. Later, Pakiza, Tuman's second wife and Maryam's co-wife, became the bane of her life. Her account captures something of the depth and colour of people's lives. It gives voice to the ensuing silence over the past nearly fifty years and offers a radical challenge to the gendered stereotypes which have dominated the global and Afghan media during the past forty years of war and occupation.